Signs of a Future Transformation in Mission - Motte, Mary (2019)
In his gestures, choices, and words Pope Francis offers a new path for missionary transformation. This new path is rooted in his recognition that he is a sinner and in need of the mercy of God. From this space of lowliness he invites all Christians to recognize their calling as missionary disciples in a time of ongoing missionary conversion. He recognizes the necessity of ecumenical and interreligious collaboration in discovering a way to communicate the Gospel, which is rooted in the culture of encounter, is based upon the experience of authentic contemplation, and always has a place for others.
Keywords: Pope Francis; Creation; Ecumenism; missionary transformation; ongoing missionary conversion; the poor